Idosos hospitalizados: satisfação com os cuidados de Enfermagem. - Lima Junior, José de Ribamar Medeiros (2015)
Aging is considered a natural process, dynamic, progressive and irreversible, since every living thing grows old in a unique way. The rapid growth of the elderly population leads to increased demand for health services, satisfaction of the elderly is defined as the degree of congruence between the assistance provided by the health team and the reflections of care they received. The research aimed to know the level of satisfaction of elderly hospitalized with nursing care. For such a descriptive, xploratory research was conducted, crosssectional and quantitative approach 102 elderly patients, at least five days in the medical clinic of the University Hospital Presidente Dutra (HUPD) in São Luís, from April to October 2014. Data collection was performed using a questionnaire relating to demographic and economic partners aspects and also the Patient Satisfaction Instrument (PSI). The collected data were entered into spreadsheets in Microsoft Excel® 2010 program; after that, they were imported into a statistical processing software (Stata® - Version 12) in which tables were generated. The study followed the Resolution 466/12 of the National Health Council. The results showed a higher number of elderly men, aged between 60 and 69 years old, married, with up to five years of study, and to a lesser extent had eighteen years or more of schooling, family income between 01-03 times the minimum wage. As for religion, most respondents were Catholic, with a small difference from evangelicals. It was found a good level of satisfaction of elderly with nursing care, and the field of trust with the highest average, followed by the echnical-professional area and the level of overall satisfaction and satisfaction by area, above the midpoint of the Likert Scale . It was identified that satisfaction was significant in the correlation between the fields and variables "sex" and "age" of the elderly. It was found that the elderly were satisfied with the care provided by nursing and the nursing work influence the satisfaction of hospitalized elderly and stressed the importance of a competent performance, through the use of their technical skills, scientific knowledge